(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article considers the questions connected with the fact that every literary work, building the intertextual field, creates its own cultural history, redesigns the whole previous culture fund. The article attempts to cover the problem whether the works created in the same historical period relying on the previous literary experience can form the style of the epoch and special type of the image of the author. Being guided by the theory of intertextuality and using the elements of the intertextual analysis, it is possible to interpret the individual picture of the world formed by creative imagination of the artist through the prism of functions of intertext links in different works, revealing thereby features of style of a certain era. The article also considers three points of view on the prospect of narration or the category of narrator: 1) the prospect is a way of narration or narrative technique; 2) the prospect is the historical point of view of the writer, his method of perception of reality; 3) the prospect is the category covering the whole creative process of the writer.